A Comparative Study on the Nutrients in Organic Fertilizers and Garden Soil in Tirunelveli - Sakthi , Viji Siva; Jeyapraba, L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Organic fertilizers are natural compounds made from waste or by-products and human assistance is limited to physical extraction or processing steps. Examples of commonly used organic matter include sewage sludge, food processing waste, composted animal manure, and urban biosolids. In this study, an attempt was made to examine the nutritional value of Lyroderma lyra (giant pseudo-vampire bat) bat guano, garden soil, and earthworm compost. Essential elements (macro elements - N, P, K, NO3, NO2, Pi, PO3), trace elements (Na, C, Fe, Mn, Zn, Cl), meso elements (Mg, Ca, SO4)) from this study The identified non-essential elements (Al), toxic elements (Ba) and pH were analysed and compared. Earthworm compost is rich in No3, No2, Pi, PO3, Ca, Mg, SO4, C, Fe, Zn, Mn and Cl. On the other hand, bat guano is rich in N, K and Na. The garden soil was rich in Cl, Mg, Ca, N. No toxic element was found in the garden soil but found in very low levels in both vermicompost and bat guano. In summary, these elements improve soil health and gradually release necessary nutrients into the soil as essential elements. This study suggests the need for prior soil studies and the need to better balance the effects of different organic matter on plant growth.